Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.vetmic.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the course of Mycoplasma bovis infection in naturally infected dairy herds

Abstract: Mycoplasma bovis causes bovine respiratory disease, mastitis, arthritis and otitis. The importance of M. bovis has escalated because of recent outbreaks and introductions into countries previously free of M. bovis. We characterized the course of M. bovis infection on 19 recently infected dairy farms over 24 months. Our objective was to identify diagnostic tools to assess the efficacy of control measures to assess low risk infection status on M. bovis infected farms. PCR assays and culture were used to detect M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 28 publications
(24 reference statements)
2
45
0
Order By: Relevance
“…Depending on the obtained results, the PCR technique was appeared as an excellent directly method in the diagnosis of Mycoplasma and principally M. bovis from pneumonic lungs, without the demands for culturing microorganism, which is accurate method and will reduce the consuming time and efforts. Many global studies supported the use of PCR instead of the culturing or together for diagnosis of Mycoplasma and particularly M. bovis [39][40][41][42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the obtained results, the PCR technique was appeared as an excellent directly method in the diagnosis of Mycoplasma and principally M. bovis from pneumonic lungs, without the demands for culturing microorganism, which is accurate method and will reduce the consuming time and efforts. Many global studies supported the use of PCR instead of the culturing or together for diagnosis of Mycoplasma and particularly M. bovis [39][40][41][42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that M. bovis has the ability to spread worldwide to countries for a long time considered free of the pathogen because of the widespread international trade in cattle [ 2 , 23 , 24 ]. The first case of M. bovis infection in Finland was recorded relatively recently in 2012 in pneumonic calves.…”
Section: Current Reports On the Epizootic Situation Of Mmentioning
confidence: 99%
“…In 2012–2015, 0.26% of Finnish dairy farms were M. bovis infected [ 2 ]. To date, it is estimated that only 0.8% of Finnish dairy herds were infected with M. bovis between 2012 and 2018 [ 23 ]. A two-year survey included 19 Finnish dairy farms previously free of M. bovis showed mastitis caused by M. bovis in over 89% of all farms tested; however, only a few clinical mastitis cases were seen.…”
Section: Current Reports On the Epizootic Situation Of Mmentioning
confidence: 99%
“…Failure to detect subclinical mastitis promptly allows the infection to spread rapidly (Halasa et al, 2007;Hughes and Watson, 2018). Increasing evidence in recent years suggests that M. bovis is a major cause of severe mastitis infections (Vahanikkila et al, 2019;Murai and Higuchi, 2019;Josi et al, 2018) and that M. bovis is more frequently detected than other pathogens in subclinical mastitis (Al-Farha et al, 2017;Fox 2012;Nicholas et al, 2016). Therefore, the development of diagnostic methods that can detect subclinical mastitis at an early stage is important.…”
Section: Discussionmentioning
confidence: 99%
“…including staphylococci and streptococci, are responsible for the majority of mastitis cases. Recent studies reported that Mycoplasma bovis (M. bovis) caused mastitis in dairy cows (Rossetti et al, 2010;Wisselink et al, 2019;Appelt et al, 2019;Behera et al, 2018;Cai et al, 2005;Vahanikkila et al, 2019;Murai and Higuchi, 2019;Al-Farha et al, 2018;Al-Farha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%